8th RILEM International Symposium on Testing and Characterization of Sustainable and Innovative Bituminous Materials - Canestrari, Francesco; Partl, Manfred N. (RILEM Bookseries, 2016)
This work presents the results of RILEM TC 237-SIB (Testing and characterization of sustainable innovative bituminous materials and systems). The papers have been selected for publication after a rigorous peer review process and will be an invaluable source to outline and clarify the main directions of present and future research and standardization for bituminous materials and pavements. The following topics are covered: - Characterization of binder-aggregate interaction - Innovative testing of bituminous binders, additives and modifiers - Durability and aging of asphalt pavements - Mixture design and compaction analysis - Environmentally sustainable materials and technologies - Advances in laboratory characterization of bituminous materials - Modeling of road materials and pavement performance prediction - Field measurement and in-situ characterization - Innovative materials for reinforcement and interlayer systems - Cracking and damage characterization of asphalt pavements - Recycling and re-use in road pavements This is the proceedings of the RILEM SIB2015 Symposium (Ancona, Italy, October 7-9, 2015). .